Efektivitas Model TGT Berbantuan Question Box terhadap Hasil Belajar IPA Kelas V SDN 19 Palembang - Indy Deraya Ajiba; Lukman Hakim; Dina Sri Nindiati; Nanang Winarno (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research aims to determine the effectiveness of question box- assited tgt model on class v science learning outcomes of sdn 19 palembang. This type of research is quantitative research with experimental methods in the form of Quasi Experimental with a Nonequivalent Control Group Design research design. The population in this study was all class V consisting of 2 classes and totaling 56 people. Determining the sample in this research uses a purposive sampling technique, so there are 2 classes, namely V.A as the experimental class and V.B as the control class. The form of data collection technique is using observation, test and documentation techniques. In observations, the average student score was 87.05% with good criteria and the average teacher score was 90% with very good criteria. The data analysis technique uses parametric statistical tests through the N-Gain hypothesis test and the N-Gain test. The N-Gain hypothesis test used the Independent Sample T-Test which obtained t_count = 2.924 and t_table = 2.004 and a 2 tailed significant value of 0.005. Thus, the T test results show that 2,924 > 2,004 and the significant value is 0.005 (<0.05), so it can be concluded that H_0 is rejected and H_a is accepted. Meanwhile, looking at N-Gain value for the experimental class, it was found to be 0.6573 or 66%, which is included in the medium category. Meanwhile, the average N-Gain value for the control class was 0.4181 or 42%. Based on the research results obtained, the application of the Teams Games Tournament (TGT) model assisted by Question Box media to student learning outcomes in Class V science subjects at SD Negeri 19 Palembang is quite effective.